ANALISIS KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR GENERASI MILENIAL DAN GENERASI Z DI KECAMATAN MENTOK - Noviansyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Elementary education faces significant challenges in the digital era, where teachers are required to possess professional competencies that not only include mastery of subject matter but also the ability to adapt to technological developments and the characteristics of digital-native students. This study aims to analyze the competencies of Millennial and Generation Z teachers in public elementary schools in Mentok District in responding to educational challenges, and identify the forms of professional competence implemented by both generations in classroom practices. This research employed a qualitative descriptive approach, using observation, interviews, and documentation involving elementary school teachers in Mentok District. The findings reveal that Millennial teachers demonstrate professional competence through systematic lesson planning, reflection, discipline, and moral exemplification. Meanwhile, Generation Z teachers highlight creativity, flexibility, and the use of digital tools such as Canva, Kahoot, and Quizizz to foster more interactive learning. These differences are not barriers but rather opportunities for collaboration: Millennial teachers provide stability and moral values, while Generation Z teachers offer digital innovation and interactivity. Therefore, cross-generational collaboration is a strategic approach to enhancing teacher professionalism and improving the quality of elementary education in the digital era.